2006
DOI: 10.1111/j.1742-4801.2006.00210.x
|View full text |Cite
|
Sign up to set email alerts
|

Burn wound depth assessment – is laser Doppler imaging the best measurement tool available?

Abstract: Accurate early assessment of burn wound depth is increasingly important in clinical decision-making. Clinimetric principles are absolutely mandatory while developing a new test or tool for use in the clinical setting. This article critically evaluates the clinimetrics of a powerful tool for assessment of burn depth and whether Laser Doppler Imaging can meet those criteria by virtue of differentiation between superficial and deep burns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Early studies using the laser Doppler monitoring technique showed a strong correlation between skin blood flow and healing time or need for surgery [6][7][8]. The laser Doppler imaging technique for skin blood flow mapping was introduced by Niazi et al [9] and has become more widely used to aid routine burn assessments [5,[10][11][12] and comparison of treatments [13,14] in recent years.…”
Section: Introductionmentioning
confidence: 98%
“…Early studies using the laser Doppler monitoring technique showed a strong correlation between skin blood flow and healing time or need for surgery [6][7][8]. The laser Doppler imaging technique for skin blood flow mapping was introduced by Niazi et al [9] and has become more widely used to aid routine burn assessments [5,[10][11][12] and comparison of treatments [13,14] in recent years.…”
Section: Introductionmentioning
confidence: 98%
“…Without early intervention, some partial thickness burns progress to full thickness injuries, exposing the patient to substantial morbidity and undergoing excision and grafting [2]. Despite multiple advances in acute treatment and surgical management, the decision to debride a burn still largely relies on the experience and visual perception of the individual surgeon [3]. Because early clinician accuracy is limited, ranging The current standard of care in determining the need to excise and graft a burn remains with the burn surgeon, whose clinical judgment is often variable.…”
Section: Introductionmentioning
confidence: 99%
“…Disruption of this blood flow correlates with the extent of injury, and is displayed by a colour map of the wound. This is then interpreted alongside the clinical examination findings or digital photographs when assessing depth [11,12]. To date, LDI remains the only evidence-based adjunct supported by the National Institute for Health and Care Excellence (NICE) [13].…”
Section: Introductionmentioning
confidence: 99%